Cyclical adjustment, capital-labor substitution and total factor productivity convergence - East Germany after unification - Werner Smolny (Verein für Socialpolitik, 2010)
Despite rapid economic integration and massive help from the Federal Government East German productivity catching up faded out in the nineties. This paper presents panel-data estimates of the productivity adjustment based on a production function framework and a stylized adjustment model of the economy. The central empirical result is a decomposition of the sources of productivity growth. The estimates reveal that a large part of productivity growth in the early nineties is related to factors that were specific for those period. The fading out since the mid-nineties is attributed to the development of total factor productivity.
Keywords: O11; O47; P20; 330; Economics of transition; productivity convergence